Deployment of Six Sigma Methodology in Pars Plana Vitrectomy - Sahbaz, Ibrahim; Taner, Mehmet Tolga; Sanisoglu, Huseyin; Kar, Taner; Kagan, Gamze; Durmus, Ebubekir; Tunca, Meltem; Erbas, Engin; Armagan, Ilker; Kagan, Mehmet Kemal (International Journal of Statistics in Medical Research, 2014)
Purpose: To show how a Turkish public eye care centre in Turkey initiated Six Sigma principles to reduce the number of complications occurring during and after pars plana vitreoretctomy surgeries. Method: Data were collected for two years. To analyse the complications among 2272 patients, main tools of Six Sigma’s Define-Measure-Analyse-Improve-Control (DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Sources and root causes of twenty-two types of complications were identified and reported. Results: For a successful pars plana vitrectomy procedure, experience of vitreoretinal surgeon, attention of vitreoretinal surgeon, patient’s anatomy were determined to be the “critical few” factors whereas, sterilization and hygiene, amount of silicone oil and amount of gas were found to be the “trivial many” factors. The most frequently occurring complication was found to be subconjunctival haemorrhage. Conclusion: The sigma level of the overall process was measured to be 3.8559. The surgical team concluded that twelve of the complications should be significantly reduced by taking the necessary preventive measures. Institutional ethics committee approval has been taken due to retrospective nature of this study.